Beta-Blocker Therapy for New-Onset Hypertension Following an Electrical Injury: A Case Report - Yang, Ho-Dong; Han, Donghoon; Shin, Dong Geum; Kang, Min-Kyung; Cho, Jung Rae; Choi, Seonghoon; Lee, Jong-Wook; Lee, Namho (Archives of Clinical and Medical Case Reports, 2020)
Electrical injuries may occur in both home and workplace environments leading to cardiovascular complications, such as tachyarrhythmia, bradyarrhythmia, atrial fibrillation and myocardial injury. However, reports on electrical injury induced hypertension are rare. The choice of appropriate antihypertensive agents is therefore unclear. As described in this report, beta-blockers may be useful in hypertension induced by electrical injuries.